Luminescent Oxygen-Sensitive Ink to Produce Highly Secured Anticounterfeiting Labels by Inkjet Printing - Ding, Longjiang; Wang, Xu-dong (Journal of the American Chemical Society, 2020)
A new covert luminescent anticounterfeiting (AC) technology was developed by employing combinatorial chemistry and concentration-dependent stimulus-responsive luminescent patterns. Oxygen-sensitive materials are carefully tailed to be inkjet printable and to form luminescent color inks. The inks are placed in the tanks of a jet printer. The printed luminescent patterns exhibited multilevel and highly secured AC features. Unlike conventional luminescent AC technology that solely relies on luminescent molecules/nanoparticles, the new technique utilizes the following features to fight counterfeiting: (1) the combination of luminescent oxygen-sensitive probes (OSPs) and the oxygen-permeable matrix (OPM), (2) the unique nonlinear oxygen-responsive behavior, (3) the local oxygen concentration, and (4) a luminescence lifetime reading device. The virtually unlimited number of codes is mainly due to the following features: (a) an almost endless number of combinations of OSPs and OPMs and (b) the nonlinearity of the Stern–Volmer plots that describe quenching of luminescence by oxygen. This combinatorial chemistry strategy makes it very difficult for counterfeiters to find the right composition even when the chemical composition of the luminescent molecules/nanoparticles was known. Information encrypted via this new methodology exhibits extremely high security, as counterfeiters need to identify all (not part of them) the following security measures: (1) the right combination of OSPs and OPMs, (2) the right chemical stimulus (here oxygen), (3) the proper oxygen concentration, and (4) the correct luminescence lifetime values.